Aminolysis of Lithium/Yttrium Bimetallic Alkyls including the Solid‐State Structure of a Europium(II) n‐Butyl Compound. Issue 4 (5th October 2022) - Berger, Tassilo; Baschnagel, David; Maichle‐Mössmer, Cäcilia; Anwander, Reiner
Abstract: Using previously established salt‐metathesis procedures at low temperature, heterobimetallic ate complexes Li6 Eu II ( n ‐Bu)8 (thf)6 and Li3 Y III ( i ‐Bu)6 (thf)4 could be synthesized and their solid‐state structures analyzed by X‐ray diffraction. Recently described complex Li3 Y( n ‐Bu)6 (thf)4 was probed as a precursor in protonolyses with various amines, revealing distinct reaction pathways. Identified products comprise homoleptic amide Y[HNC6 H3 (mes)2 ‐2, 6]3 (mes=C6 H2 Me3 ‐2, 4, 6), heteroleptic C−H‐bond activated Li3 Y( n ‐Bu)2 [N(SiMe2 CH2 )(C6 H3 ‐Me2 ‐3, 5)]2 (thf)5, and mixed amido/imido complex [LiY2 (HNSiPh3 )4 (NSiPh3 )2 ][Li(thf)2 (OEt2 )2 ]. Abstract :